1959
DOI: 10.1002/pol.1959.1203512904
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of poly(vinyl chloride)

Abstract: Poly(vinyl chloride), polymerized with the use of γ‐radiation, benzoyl peroxide, and 2,2′‐azobis(isobutyroitrile) as initiators, was thermally decomposed in vacuo. The gaseous decomposition products as analyzed by mass spectrometry consist primarily of hydrogen chloride for decomposition temperatures below approximately 300°C. At temperatures approximating 400°C., various hYdrocarbons are evolved along with the hydrogen chloride. Energetic considerations are discussed and the activition energy is determined. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(40 citation statements)
references
References 13 publications
4
33
0
Order By: Relevance
“…This result suggests that the activation energy of cross-linking dehydrochlorination is lowered in the presence of ZnO. Hendrikse et al [25,26] There have been many kinetic studies [1,4,11,22,24] for the dehydrochlorination of pure PVC, and the activation energy of the dehydrochlorination 1 is 109-134 kJ mol -1 .…”
Section: Ir Spectramentioning
confidence: 96%
See 1 more Smart Citation
“…This result suggests that the activation energy of cross-linking dehydrochlorination is lowered in the presence of ZnO. Hendrikse et al [25,26] There have been many kinetic studies [1,4,11,22,24] for the dehydrochlorination of pure PVC, and the activation energy of the dehydrochlorination 1 is 109-134 kJ mol -1 .…”
Section: Ir Spectramentioning
confidence: 96%
“…It is widely accepted that the first step of thermal decomposition of PVC is polyene formation accompanying evolution of a large quantity of HCl gas [1][2][3][4][5][6]. The polyene once formed easily turns to aromatic compounds such as benzene and toluene via C-C bond cleavage.…”
mentioning
confidence: 99%
“…This is charac terisLic of polym ers in which th e loss of side groups from a.d jacent carbons of th e ch ain r esults in conjugated double bonds in the ch ain, sin ce th ese double bonds tend to enhance th e th ermal sLability of Lhe chain. Polyvinyl chlorid e [12] and polyviJ1~TlideJ1e fluoride [13] may b e cited a.s examples of a behavior similar to t hat of polyacrylon itrile.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrogen cyanide most likely forms by spli tting-off the chain in the same manner as CH3COOH in the pyrolysis of polyvin yl acetate [11], H Cl in tbe pyrolysis of polyvinyl chloride [12], and HF in the pyrolysis of hydroAuoroethylene polymeTs [13]. Formation of monomer can b e visualized as follows.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that practically all HCI (60 wt%) is released by the time the sample has reached 220~ (Turi 1981). Thermogravimetricmass spectrometric (TG-MS) studies have shown that the degradation products of PVC were composed of HC1, aromatics, and other hydrocarbons such as ethylene, ethane, propylene, xylene, and methane (Stromberg et al 1959;Mardosky 1964). The first weight loss observed in Fig.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%